Sensory Marketing at the Destination Level: A Conceptual Approach - Ricardo Fontes CORREIA; Ana FRANCO; Raquel MENESES (Communications of International Proceedings, 2020)
Marketing strategies adopted in many destinations do not take into consideration the potential of the senses to generate memorable experiences. By ignoring a driving force of intangibility, such strategies do not value a major source of differentiation. In fact, in a time where the intangible assumes an essential role, the senses emerge as a key for the differentiation of a particular destination when compared to other alternatives. This article puts in evidence the importance of the sensory marketing at the destination level. We develop a conceptual model where sensory contact points emerge as the central element in the 3 different phases of the tourist experience: a priori to capture the attention and provide (or recall) sensations of the destination, in loco for the generation of a multisensory image of the destination, and a posteriori inspiring a new visit to the destination or it’s recommendation to others. The model proves to be particularly useful for practitioners, offering relevant insights for managers and policy makers.
Keywords: Sensory Marketing; Senses; Destination; Tourism; Experiences.